The effect of vitamin D on airway reactivity and inflammation in asthmatic children: A double‐blind placebo‐controlled trial. Issue 8 (2nd July 2014) - Bar Yoseph, Ronen; Livnat, Galit; Schnapp, Zeev; Hakim, Fahed; Dabbah, Husein; Goldbart, Aviv; Bentur, Lea
Summary Background Cross‐sectional studies have reported an association of vitamin D deficiency with increased asthma prevalence and severity, and with allergies. The effect of vitamin D as sole therapy on airway hyper‐reactivity (AHR) and airway inflammation has not been reported. Aim To evaluate the effect of vitamin D therapy on AHR as assessed by methacholine concentration, causing a 20% reduction in FEV1 (PC20‐FEV1) and fractional exhaled nitric oxide (FeNO), systemic markers of allergy and inflammation, and exhaled breath condensate cytokines. Patients and Methods Children aged 6–18 years with a clinical diagnosis of mild asthma currently not receiving anti‐inflammatory therapy and with low vitamin D levels were included in this randomized, double‐blind, placebo‐controlled study assessing the effect of 6 weeks of treatment with oral vitamin D 14, 000 units once weekly or placebo. Results Of the 39 patients included, 20 received vitamin D treatment and 19 received a placebo. Vitamin D replacement resulted in a significant increase in vitamin levels, which remained unchanged in the placebo group (P < 0.0001). There was no change in IgE, eosinophil count, high sensitivity C‐reactive protein, FeNO levels or PC20‐FEV1 following treatment. Similar values of exhaled breath condensate cytokines (IL4, IL5, IL10, IL17, and γ interferon) were observed in both groups. Conclusions In our small group of children with mild asthma, no difference could be demonstrated between the effect of vitamin D and placebo, despite significant increases in vitamin D blood levels. Larger interventional studies are needed to fully explore the possible effect of vitamin D in asthma. Pediatr Pulmonol. 2015; 50:747–753. © 2014 Wiley Periodicals, Inc.